Genetic Screening and Expression Analysis of Psychrophilic Bacillus spp. Reveal Their Potential to Alleviate Cold Stress and Modulate Phytohormones in Wheat - Muhammad Zubair; Alvina Hanif; Ayaz Farzand; Taha Majid Mahmood Sheikh; Abdur Rashid Khan; Muhammad Suleman; Muhammad Ayaz; Xuewen Gao (Microorganisms, 2019)
Abiotic stress in plants pose a major threat to cereal crop production worldwide and cold stress is also notorious for causing a decrease in plant growth and yield in wheat. The present study was designed to alleviate cold stress on plants by inoculating psychrophilic PGPR bacteria belonging to Bacillus genera isolated from extreme rhizospheric environments of Qinghai-Tibetan plateau. The genetic screening of psychrophilic Bacillus spp. CJCL2, RJGP41 and temperate B. velezensis FZB42 revealed presence of genetic features corresponding to cold stress response, membrane transport, signal transduction and osmotic regulation. Subsequently, the time frame study for the expression of genes involved in these pathways was also significantly higher in psychrophilic strains as analyzed through qPCR analysis at 4 ℃. The inoculated cold tolerant Bacillus strains also aided in inducing stress response in wheat by regulating abscisic acid, lipid peroxidation and proline accumulation pathways in a beneficial manner. Moreover, during comparative analysis of growth promotion in wheat all three Bacillus strains showed significant results at 25 ℃. Whereas, psychrophilic Bacillus strains CJCL2 and RJGP41 were able to positively regulate the expression of phytohormones leading to significant improvement in plant growth under cold stress.